Aplikasi Bimbingan Belajar Bahasa Inggris Tingkat Sekolah Dasar (SD) Dengan Fitur Live Chat Dan Automatic Essay Scoring - Destu Adiyanto; Viny Christanti Mawardi; Manatap Dolok Lauro (Fakultas Teknologi Informasi Universitas Tarumanagara, 2022)
In the current pandemic, parents want to do additional learning for their children. Therefore, a research was conducted with the title of Application of English Tutoring for Elementary School Level (SD) with Live Chat and Automatic Essay Scoring features and is expected to help the learning carried out by teachers and students. The hope of this application can be useful and can make it easier for teachers to find places to do learning. The system created today is a scoring system in the form of an essay where when students solve problems in the current system it will produce points per question worked on and the total points will produce the correct number of points. Experiments were carried out with several students with several similar questions to find out whether the designed system worked as expected or not. By conducting three trials on students with the same 10 questions and with K-Gram 3, 4 and 5. 4 which was carried out, the results were 70% and for the accuracy results from the K-Gram 5 experiments carried out, the results were 65%.